2016
DOI: 10.1016/j.aap.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle helmet use and the risk of head, neck, and fatal injury: Revisiting the Hurt Study

Abstract: Most studies find strong evidence that motorcycle helmets protect against injury, but a small number of controversial studies have reported a positive association between helmet use and neck injury. The most commonly cited paper is that of Goldstein (1986). Goldstein obtained and reanalyzed data from the Hurt Study, a prospective, on-scene investigation of 900 motorcycle collisions in the city of Los Angeles. The Goldstein results have been adopted by the anti-helmet community to justify resistance to compulso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 16 publications
4
26
0
4
Order By: Relevance
“…Studies [1,[5][6][7][8][9] have consistently concluded that helmet use is beneficial in preventing head injuries and subsequently reducing injury severity among motorcyclists. By using police-reported crash data in Taiwan, Keng [10] found that helmet use was associated with a decreased odds of deaths among motorcyclists.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [1,[5][6][7][8][9] have consistently concluded that helmet use is beneficial in preventing head injuries and subsequently reducing injury severity among motorcyclists. By using police-reported crash data in Taiwan, Keng [10] found that helmet use was associated with a decreased odds of deaths among motorcyclists.…”
Section: Introductionmentioning
confidence: 99%
“…The impact point B was chosen because it is the most common impact. Statistics show that independently of the helmet type, this is the most impacted area [57][58][59][60][61][62][63][64]. In addition, in the previous section, this was the impact point where the EPS helmet had lower accelerations (Figure 4).…”
Section: New Helmet and Its Optimizationmentioning
confidence: 87%
“…La mayor gravedad encontrada entre los conductores que no usaban casco en el momento del accidente concuerda con lo encontrado en numerosas investigaciones que señalan como la utilización del casco reduce el riesgo de lesiones en la cabeza y la cara, así como de fallecimiento en caso de accidente (Ha et al, 2018;Moskal, Martin & Laumon, 2008;Rice et al, 2016).…”
Section: Discussionunclassified